Potential Application of Superabsorbent Hydrogel Composite in Geotechnical Engineering Focusing Sustainability: State-of-the-Art Review - Saha, Abhisekh; Sekharan, Sreedeep (Indian Geotechnical Journal, 2024)
Superabsorbent hydrogel composite (SHC), an innovative, bio-renewable, three-dimensional (3D) interpenetrating polymer network, is gaining attention in the field of geotechnical engineering due to its superhydrophilic characteristics. The presence of various hydrophilic groups in the polymeric structure of SHC facilitates excellent water absorbency (> 100 times its own weight) and serves as an additional mini-water reservoir inside the soil matrix to maintain vegetation covers on geotechnical infrastructures under arid conditions. This state-of-the-art review aims to identify potential application of SHC to promote sustainable geotechnics through waste-to-resource conversion, development of self-sustaining green infrastructure, ecological restoration of polluted land, effective management of dredged soil, and development of composite barrier layer for underground waste containment facilities. The review paper identifies the thrust research areas in sustainable geotechnics and maps those with sustainable development goals (SDGs) formulated by United Nations General Assembly (UNGA) in 2015. A brief description of SHC synthesis from various industrial, agricultural, and ocean waste is presented and classified the waste based on their composition for SHC synthesis. Efforts were made to develop critical understanding of soil–water retention capacity and vegetation growth in SHC-amended soils. The current understanding and the gap in knowledge related to the ion adsorption ability and swelling of SHC under extreme environmental conditions (i.e., hyper-alkaline, hyper-acidic, and high saline) are discussed. The major research gaps and future perspectives of SHC in sustainable geotechnics are put forth that need to be addressed.